Perception of accountants on the application of International Public Sector Accounting Standards (IPSASS) in Tanzanian local government authorities: A case of Manyara Region - Chibunu, Wictory E. (Mzumbe University, 2024)
A Dissertation is submitted in Fulfillment of the Requirements for the Degree of Masters of Science in Accounting and Finance (MSc. A&F) of Mzumbe University